The effect of oxygenated water in Diabetes Mellitus (Faculty of Medicine Universitas Indonesia, 2009)
Aim To examine those claims, i.e the effects of oxygenated water on hypertension and Diabetes Mellitus (DM).Methods In this clinical trial, 108 subjects of Diabetes Mellitus were recruited. Each group was divided randomly into 2 subgroups. One subgroup was given oxygenated water and the other subgroup was given non-oxygenated water for 2 period of intervention, 45 days and 90 days. Measured variables were, blood sugar and malondialdehyde (MDA).Results The study showed that oxygenated water could reduce post-prandial glucose in DM subjects. DM subjects with normal nutritional states, also had greater tendency of MDA reduction after consuming oxygenated water for 45 days. Most of subjects felt healthier after consuming oxygenated water.Conclusion The consumption of oxygenated water could improve the healing process for patients with diabetes mellitus. (Med J Indones 2009; 18: 102-7)Key words: oxygenated water, diabetes mellitus, MDA, free radicals